Postoperatory Complications in Appendectomies - Croci, Fabio; Besenzoni, Raúl; Montandon, Juan Carlos; Costa, José (Cirugía del Uruguay, 1980)
In a series of 240 appendectomies, 28 o/o suffered. from postoperatory complications; 5 % of them were serious but no fatalities occurred.